Different neutrophil extracellular trap related Ewing sarcoma subtypes exhibit distinct prognosis, and immune microenvironment characteristics - Shihao Li; Yanli Hou; Lina Zhang; Haiyang Zhang; Congcong Wang (Scientific Reports)
Abstract Ewing sarcoma (EWS) is a rare bone cancer that is most usually detected in children. Neutrophil extracellular traps (NETs) are closely related to the prognosis of cancer, but the significance of NET-related features in EWS remains uncertain. We constructed a NET signature utilizing four crucial NET-related genes in EWS to forecast prognosis and investigate the potential immunological value of this signature in EWS. EWS data were collected from the International Cancer Genome Consortium and Gene Expression Omnibus databases. We identified the subtypes mediated by NET-related genes in EWS and analyzed the function infiltration and immune signature of NET-related subtypes in EWS. The expression levels of proteins in EWS cells were detected via western blotting analysis. NET could distinguish EWS patients into two NET-related subtypes: C1 and C2. EWS patients with the C1 subtype exhibited a more unfavorable prognosis and higher levels of TIDE and T cell dysfunction when compared to individuals with the C2 subtype. C1 and C2 subtypes had different immune characteristics. A NET-related prognostic model including AKT1, MAPK3, ATG7, and SELPLG was established to predict the prognosis of EWS patients. The risk score model was an independent prognostic factor for EWS, and high-risk EWS patients exhibited significantly inferior prognosis. AKT1 and ATG7 expression was significantly increased in EWS samples. The protein levels of AKT1 and ATG7 were increased in EWS cells, while the protein levels of SELPLG was decreased. The NET-related prognostic model is a critical biomarker for predicting prognosis, defining molecular subtypes, and describing immune signatures in patients with EWS.